Efficacy of auricular and electronic acupuncture to treat chronic low back pain: A randomised trial - Diem Huong Thi Nguyen; Son Thi Nguyen; Minh Quan Hoang Le; Ngoc Nghia Thi Nguyen; Thuong Hoai Nguyen; Bao Ngoc Le; Thuc Anh Ho (Vietnam Journal of Science, Technology and Engineering)
Chronic low back pain (CLBP) imposes significant medical treatment costs and leads to numerous serious health consequences. In recent years, non-pharmacological therapies have garnered increasing attention, particularly electroacupuncture (EA) and auricular acupuncture (AA). While considerable research has examined the efficacy of EA and AA in managing CLBP, it may be beneficial to investigate the impact of combining these approaches. This study focuses on the efficacy of a combined AA and EA treatment for CLBP compared to EA alone. This randomised, double-blind, controlled trial allocated 80 patients into two groups: one receiving EA in conjunction with AA at the target points Shenmen (TF4), Lumbosacral Vertebrae (AH9), and Subcortex (AT4), and the other receiving EA with sham AA (AA applied at non-acupoint locations). Pain intensity, functional disability, and spinal mobility were assessed using the visual analogue scale (VAS), Oswestry disability index (ODI), and Schober index at baseline (T0), after 7 days (T7), and after 14 days (T14). While both groups exhibited improvement, the intervention group demonstrated a greater reduction in VAS scores (T14: 1.65±0.66 vs. 3.28±0.91, p<0.001) and ODI scores (T14: 13.98±1.43 vs. 17.45±1.74, p<0.001), alongside a significant increase in spinal flexibility (Schober index: 14.66±0.80 vs. 13.43±1.04, p<0.001). In conclusion, among patients with CLBP, the combination of AA and EA resulted in more effective pain relief and greater improvement in spinal function compared to EA alone.